Digital Preservation in the Perspective of Knowledge and Information Technology: A Systematic Literature Review - Alfanzha, Figo Alief; Lawanda, Ike Iswary (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
Cultural heritage has valuable information that is maintained in ensuring the continuity of information from a culture. One form of activity that can be carried out to maintain cultural heritage is preservation. Preservation is an activity that aims to store and managing information contained in an object or document. In the era of development of information technology, the use of technology in preservation is also utilized to help maintain cultural heritage, namely by carrying out digital preservation activities. Digital preservation is a method that plays a role in maintaining and managing information collections by transferring media, creating storage and access to the information in order to ensure that cultural heritage can be stored for a long period of time and can be widely accessed. In carrying out digital preservation, the factors that support the success of digital preservation are closely related to the existence of science and information technology. Information technology has the advantage of being able to maintain the stability of stored information, ease of free access to information, and extensive storage space. There are other methods and factors that are considered in the use of technology for digital preservation, such as the use of devices, in information technology that are related to knowledge preservation practices in institutions. This research aims to understand the role of science and information technology in digital preservation activities. This research uses a systematic review method of related articles. The results of the systematic review shown the role of information technology in digital preservation activities and maintaining the cultural heritage.